Analisa Ekonomi Pendirian Pabrik Arang Aktif dari Biji Salak - Handoko, Rinto Erwin; Anggraini, Sinar Perbawani Abrina; Mediaswanti, Kun Aussieanita (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Demand for activated charcoal in Indonesia is increasing along with advances in technology and industry in this country. This increasing need must be supported by researchers and entrepreneurs working in the field of activated charcoal to produce activated charcoal that is good in terms of quality and quantity. To meet domestic demand, this activated charcoal factory was established. The aim of this research is to determine the feasibility of establishing an activated charcoal factory based on economic analysis. Production capacity in the factory establishment is planned to be 9,000 tons / year. This factory operates 300 days a year. An activated charcoal factory is planned to be built in Malang Regency, East Java Province in 2026. The main tool used in building an activated charcoal factory from salak seeds is a mixer. Process utilities include the supply of process water, electricity, cooling water and fuel. Return On Investment (ROI) before tax 87% and after tax 79%. Pay Out Time (POT) 1.2 years, Break Event Point (BEP) 39.13%, Shut Down Point (SDP) 23.05%, Internal Rate Return (IRR) 35.6%. From the analysis data above, it can be concluded that this factory is worthy of being established in Indonesia. Abstrak Permintaan akan arang aktif di Indonesia meningkat seiring dengan kemajuan teknologi dan industri di negara ini. Kebutuhan yang semakin meningkat ini harus didukung oleh para peneliti dan pengusaha yang bekerja di bidang arang aktif untuk memproduksi arang aktif yang baik dari segi kualitas dan kuantitas. Untuk memenuhi permintaan domestik, pabrik arang aktif ini didirikan. Tujuan dari penelitian ini adalah untuk menentukan kelayakan pendirian pabrik arang aktif berdasarkan analisa ekonomi. Kapasitas produksi dalam pendirian pabrik direncanakan 9.000 ton / tahun. Pabrik ini beroperasi selama 300 hari setahun. Pabrik arang aktif direncanakan akan dibangun di Kabupaten Malang, Provinsi Jawa Timur pada tahun 2026. Alat utama yang digunakan dalam membangun pabrik arang aktif dari biji salak adalah Mixer. Proses utilitas antara lain pasokan air proses, listrik, air pendingin dan bahan bakar. Return On Investment (ROI) sebelum pajak 87% dan setelah pajak 79%. Pay Out Time (POT) 1,2 tahun, Break Event Point (BEP) 39,13%, Shut Down Point (SDP) 23.05%, Internal Rate Return (IRR) 35,6%. Dari data analisis di atas dapat disimpulkan bahwa pabrik ini layak didirikan di Indonesia.